Well-Being Among Sexual and Gender Minority Victims of Intimate Partner Violence: A Scoping Review - Hannah R. Seidman; Ivy K. Ho (LGBT Health, 2026)
Purpose: This review aimed to provide an overview of the well-being outcomes identified among sexual and gender minority (SGM) victims of intimate partner violence (IPV). Methods: This review followed the Preferred Reporting Items for Systematic reviews and Meta-Analyses guidelines for scoping reviews. Results were extracted from APA PsycInfo, APA PsycArticles, CINAHL, CINAHL Plus with Full Text, and MEDLINE. Studies were included if participants were aged 18 or older, identified as a sexual and/or gender minority person, and experienced IPV victimization; the study investigated one form of well-being; data analysis focused on SGM individuals; publications were in English; and the study was published from January 1, 2001 to September 26, 2024. Studies were excluded if they were conducted outside the United States; the population did not include SGM individuals; participants were younger than age 18; and only IPV perpetration was studied. Two screening phases were conducted, producing 33 studies. Data from each study were extracted, organized, and synthesized in Microsoft Excel. Results: The 33 studies revealed negative physical (HIV and sexually transmitted infections, insomnia), mental and emotional (depression, anxiety, post-traumatic stress disorder), and economic (healthcare, housing, and phone/internet insecurity) well-being outcomes among SGM IPV victims. Conclusion: Findings from the articles included in this review support associations between IPV victimization and poorer well-being among SGM populations. Future research should continue exploring intersections between IPV and health among SGM populations with emphasis on cross-cultural differences, specifically outside the United States.